2020
DOI: 10.1111/jerd.12658
|View full text |Cite
|
Sign up to set email alerts
|

Fracture load of CAD/CAM ultrathin occlusal veneers luted to enamel or dentin

Abstract: Objectives To evaluate, in vitro, the fracture load of IPS e.max CAD occlusal veneers at thicknesses of either 0.3 or 0.6 mm luted to enamel or dentin. Materials and methods Fifty human molars were randomly distributed into five groups (n = 10): G1 ‐ healthy teeth (control); G2‐0.3‐mm‐thick veneers luted to enamel; G3‐0.6‐mm‐thick veneers luted to enamel; G4‐0.3‐mm‐thick veneers luted to dentin; and G5‐0.6‐mm‐thick veneers luted to dentin. After the luting procedures, the specimens were immersed in distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…17 There was no statistical significant difference between the tested substrates. This comes in accordance to Valenzuela et al (2020) 18 19 in which fracture resistance of lithium disilicate occlusal veneers with a class I cavity was higher than fracture resistance of restorations where a composite filling in the class I dentin cavity. These findings have shown that the restoration of a tooth with a lithium disilicate ceramic material does not require composite in the cavity preparation of the class I with the cavity design optimization approach.…”
Section: Materials and Methods 21 Specimen Fabricationsupporting
confidence: 91%
“…17 There was no statistical significant difference between the tested substrates. This comes in accordance to Valenzuela et al (2020) 18 19 in which fracture resistance of lithium disilicate occlusal veneers with a class I cavity was higher than fracture resistance of restorations where a composite filling in the class I dentin cavity. These findings have shown that the restoration of a tooth with a lithium disilicate ceramic material does not require composite in the cavity preparation of the class I with the cavity design optimization approach.…”
Section: Materials and Methods 21 Specimen Fabricationsupporting
confidence: 91%
“…With occlusal veneers, the dental bonding surfaces can vary greatly, and may be purely enamel, dentin, or composite fillings, and each of these bonding substrates could affect the fracture resistance differently [34,38,39]. The strength of tooth-restoration complex is influenced by the elastic moduli of the material and substrate, as well as the material's flexural resistance [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…These results may be attributed to the greater flexibility that was given to the ceramic network of the hybrid ceramics after being infiltrated with polymers which lessens the crack propagation property that was recorded as a common problem with the ceramic materials. (61,62) Many previous studies had explained the importance of the slight mismatch of the modulus of elasticity between the restoration and the supporting tissues or substrates (3,17,51,63) and its positive effect on the fracture strength of these restorations. Restorative materials that better matches the modulus of elasticity of enamel or dentin gives better stress distribution and hence better fracture resistance values.…”
Section: Discussionmentioning
confidence: 99%
“…They correlate the improved fracture resistance values of the samples bonded with selective etching technique to the stability of the adhesively bonded occlusal veneers in the enamel marginal area. (59) Valenzuela et al (3) studied the effect of reduction of the occlusal veneer thickness on fracture resistance of glass ceramics. They obtained higher fracture strength values for occlusal veneers with 0.3mm thickness than that with 0.6mm thickness regardless of the bonding substrate and they linked their results to the successful adhesive bonding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation